1991
DOI: 10.3109/01050399109070785
|View full text |Cite
|
Sign up to set email alerts
|

Central Auditory Skills in Blind and Sighted Subjects

Abstract: Three different central auditory skills were compared and evaluated in 56 blind and 40 sighted subjects. The study consisted of three experiments conducted in three subgroups. Experiment A was performed in order to evaluate the localization function; experiment B for the temporal auditory resolution ability of the blind adult, and experiment C to test the ability of the blind person to discriminate speech material in noise. In all three experiments the blind subjects obtained significantly better results than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(107 citation statements)
references
References 9 publications
9
94
0
2
Order By: Relevance
“…This is despite the fact that identical methods for threshold determination were used in both experiments. The existing literature on tactile thresholds is equally contradictive (Weinstein, 1968;Heinrich and Moorhouse, 1969;Liddle, 1969;Lindblom and Lindströ m, 1976;Warren, 1978;Bernard, 1979;Niemeyer and Starling, 1981;Bross and Borenstein, 1982;Hollins, 1989;Muchnik et al, 1991;Stevens et al, 1996), and we, therefore, conclude that neither visual deprivation nor Braille reading or the combination of both conditions is coupled with a substantial decrease of tactile perception thresholds.…”
Section: Discussionmentioning
confidence: 73%
“…This is despite the fact that identical methods for threshold determination were used in both experiments. The existing literature on tactile thresholds is equally contradictive (Weinstein, 1968;Heinrich and Moorhouse, 1969;Liddle, 1969;Lindblom and Lindströ m, 1976;Warren, 1978;Bernard, 1979;Niemeyer and Starling, 1981;Bross and Borenstein, 1982;Hollins, 1989;Muchnik et al, 1991;Stevens et al, 1996), and we, therefore, conclude that neither visual deprivation nor Braille reading or the combination of both conditions is coupled with a substantial decrease of tactile perception thresholds.…”
Section: Discussionmentioning
confidence: 73%
“…5,6 Nevertheless, while some studies have reported that blind individuals show better auditory spatial discrimination or localisation of sound sources than sighted subjects, other studies have failed to demonstrate this gain. [7][8][9][10] Recently, Finocchietti et al reported that localisation of sound in the mid-sagittal plane was poorer among blind individuals than sighted controls, indicating a clear deficit in encoding the sound motion in the lower hemisphere of the spherical coordinate system; however, the researchers confirmed that no such deficit was observed among congenitally blind subjects. 11 Voss et al confirmed that individuals who are blind demonstrated supernormal abilities in the recognition of sound sources both nearby and at a distance.…”
mentioning
confidence: 53%
“…[77][78][79] Early studies regarding the ability of the blind to localize, a binaural task of vital significance to the blind population, reveal inconsistencies in the results (see Ashmead et al 76 for a comprehensive review of spatial hearing in blind listeners). For example, Starlinger and Niemeyer 73 and Muchnik et al 80 found that blind subjects performed better than sighted listeners. Other studies of localization, however, found either no differences between the two groups or differences favoring the sighted groups.…”
Section: Auditory and Visual Localizationmentioning
confidence: 99%